Analysis of the Propagation of Defects Generated by the Oscillation Marks on Laminated Products - Stela CONSTANTINESCU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2018)
In this work was followed the determination of a method of diminishing the depth of the oscillating brands and identifying how the oscillating brands can influence the surface quality of hot rolled products (backgammon and strips). This study addresses the phenomena that take place at the initiation of the crust in the crystallizer and treats the theoretical aspects of the formation of the oscillating brands on the surface of the cast products continuously. Experiments carried out have enabled to reveal aspects regarding the relationship of oscillation brands – the quality of the products (molded or laminated) and the purity of the continuous cast slabs.